Microbial Community Succession and Metabolite Changes During Fermentation of BS Sufu, the Fermented Black Soybean Curd by Rhizopus microsporus, Rhizopus oryzae, and Actinomucor elegans - Yao, Di; Xu, Lei; Wu, Mengna; Wang, Xiaoyu; Wang, Kun; Li, Zhijiang; Zhang, Dongjie (Frontiers in Microbiology, 2021)
BS Sufu is a fermented food which is made by mixed black soybeans and soybeans. Microbial communities and metabolites play an important role for the final product. We characterized microbial diversity of BS Sufu during fermentation by high-throughput DNA sequencing. Meanwhile, volatile compounds were investigated by solid phase micro-extraction (SPME) coupled with gas chromatography-mass spectrometry (GC-MS). The results showed that bacterial diversity was higher than that of fungi in BS Sufu. We found the existence of bacterial and fungal core communities, including Enterococcus, Enterobacter, Rhizopus and Monascus, etc. Network analysis indicated that bacterial and fungal communities maintain positive and negative interactions which was important to shape the resident microbial communities in Sufu. In addition, 17 free amino acids (FAA) were detected at post-fermentation stage and umami amino acid mainly contributed to taste of BS Sufu. Furtherly, a total of 79 volatile constituents in BS Sufu, including 9 alcohols, 31 esters, 4 aldehydes etc, which form synergistically the unique odor of Sufu. Additionally, the correlations between microbiota and metabolites were analyzed. Our results suggested that these microbial taxa and metabolites contribute to taste and flavor of BS Sufu. This study provided information for analysis of BS Sufu at different fermentation period in terms of the microbial diversity and metabolites, and this information was important to understand the properties of mixed soybeans Sufu.